Protein phosphatase 2A dysfunction in Alzheimer’s disease - Sontag, Jean-Marie; Sontag, Estelle (Frontiers in Molecular Neuroscience, 2014)
Protein Phosphatase 2A (PP2A) is a large family of enzymes that account for the majority of brain Ser/Thr phosphatase activity. While PP2A enzymes collectively modulate most cellular processes, sophisticated regulatory mechanisms are ultimately responsible for ensuring isoform-specific substrate specificity. Of particular interest to the Alzheimer’s disease (AD) field, alterations in PP2A regulators and PP2A catalytic activity, subunit expression, methylation and/or phosphorylation, have been reported in AD-affected brain regions. “PP2A” dysfunction has been linked to Tau hyperphosphorylation, amyloidogenesis and synaptic deficits that are pathological hallmarks of this neurodegenerative disorder. Deregulation of PP2A enzymes also affects the activity of many Ser/Thr protein kinases implicated in AD. This review will more specifically discuss the role of the PP2A/B holoenzyme and PP2A methylation in AD pathogenesis. The PP2A/B isoform binds to tau and is the primary tau phosphatase. Its deregulation correlates with increased tau phosphorylation in vivo and in AD. Disruption of PP2A/B-Tau protein interactions likely contribute to Tau deregulation in AD. Significantly, alterations in one-carbon metabolism that impair PP2A methylation are associated with increased risk for sporadic AD, and enhanced AD-like pathology in animal models. Experimental studies have linked deregulation of PP2A methylation with down-regulation of PP2A/B, enhanced phosphorylation of Tau and amyloid precursor protein, Tau mislocalization, microtubule destabilization and neuritic defects. While it remains unclear what are the primary events that underlie “PP2A” dysfunction in AD, deregulation of PP2A enzymes definitely affects key players in the pathogenic process. As such, there is growing interest in developing PP2A-centric therapies for AD, but this may be a daunting task without a better understanding of the regulation and function of specific PP2A enzymes.